Optimalisasi Penggunaan Aplikasi Edu-Cons Pada Layanan Informasi Untuk Mengurangi Academic Burnout Mahasiswa Pada Mata Kuliah Bimbingan dan Konseling - afifatus sholihah; Syahriman Syahriman; I Wayan Dharmayana; Anna Ayu Herawati (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2023)
The academic field demands optimal learning in real contexts that have an impact on students in everyday life. That is, the learning material delivered can be applied and applied in real everyday life. In practice, students often experience various obstacles, one of which is academic burnout or often referred to as academic burnout. The application of Android-based BK learning media that has been developed in previous research produces the Edu-Cons application and is considered to be one of the learning media that can support and optimize the learning process in Android-based guidance and counseling. To overcome the problem of student academic burnout, information services are needed using the Edu-Cons application that has been made previously. The purpose of this study was to determine the level of academic burnout of students before and after being given information services using the Edu-Cons application. The research method used in this study is a pre-experimental design research. This research uses One-Group Pretest-Posttest Design. with a population of 3rd semester students of the Counseling Guidance Study Program at the University of Bengkulu with a total sample of 32 people who were determined using a random sampling technique. Data collection techniques using a questionnaire instrument. Analysis of the data in this study using the Z test which shows the value of sig(2-tailed) P <0.05 so that Ho is rejected and Ha is accepted. This means that there is an effect of information services on optimizing the use of the edu cons application to reduce student academic burnout in guidance and counseling courses.